Performance Comparison of Islamic and Conventional Banks: Empirical Evidence From Syiria During The Crisis - nour aldeen, khaled (The Pontianak State Institute of Islamic Studies, 2019)
The purpose of this research is to compare critically the performance of Islamic and conventional banks in Syria. Moreover, explore the impact of capital adequacy, liquidity, efficiency and risk management on assets performance. This study analyzed the entire private banking sector in Syria comprises 11 conventional banks and 3 full-fledged Islamic banks, over the period 2011-2017. We used paired sample t-test, correlation and multiple Regression to meet our objectives. The results suggest that Islamic banks were better in term of capital adequacy, efficiency, risk management and liquidity. While conventional banks better in terms of profitability. However, results depict that risk management performance same in Islamic and conventional banks. Private banks started in Syria since 2004. It is quite time to examine its performance because Syria is getting out of conflict era and it is important to analyze its solvency position for future prospects. This study is a pioneering attempt for analyzing banking sector in Syria, therefore, has significance for academicians, researchers and policymakers in planning works for future directions.